2019
DOI: 10.3389/fcimb.2019.00248
|View full text |Cite
|
Sign up to set email alerts
|

Fungal Kinases With a Sweet Tooth: Pleiotropic Roles of Their Phosphorylated Inositol Sugar Products in the Pathogenicity of Cryptococcus neoformans Present Novel Drug Targeting Opportunities

Abstract: Invasive fungal pathogens cause more than 300 million serious human infections and 1.6 million deaths per year. A clearer understanding of the mechanisms by which these fungi cause disease is needed to identify novel targets for urgently needed therapies. Kinases are key components of the signaling and metabolic circuitry of eukaryotic cells, which include fungi, and kinase inhibition is currently being exploited for the treatment of human diseases. Inhibiting evolutionarily divergent kinases in fungal pathoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 102 publications
(163 reference statements)
0
7
0
Order By: Relevance
“…SNP 4 was a missense variant in AFUA_5G09320, encoding a putative signal transduction protein (Syg1) with plasma membrane localization. Although the protein's function is not clear, Syg1 is predicted to be involved in phosphate homeostasis and to mediate phosphate export due to its similarity to the mammalian phosphate exporter Xpr1 [62]. The final variant site, SNP 5, was an intergenic variant located between AFUA_6G07160 and AFUA_6G07170, encoding for a putative IZH family channel protein (Izh3) and an uncharacterized protein, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…SNP 4 was a missense variant in AFUA_5G09320, encoding a putative signal transduction protein (Syg1) with plasma membrane localization. Although the protein's function is not clear, Syg1 is predicted to be involved in phosphate homeostasis and to mediate phosphate export due to its similarity to the mammalian phosphate exporter Xpr1 [62]. The final variant site, SNP 5, was an intergenic variant located between AFUA_6G07160 and AFUA_6G07170, encoding for a putative IZH family channel protein (Izh3) and an uncharacterized protein, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to this past study, we also identified pleiotropic QTGs contributing to more than one virulence-related trait examined here (including thermal tolerance and melanization), namely the genes RIC8 and SSK2. While our study did not share any of the previously implicated QTGs (Lin et al, 2006;Vogan et al, 2016), across several studies -not just those using QTL mapping strategies -observing pleiotropic effects of genes and pathways connected to virulence and virulence-associated traits seems to be a unifying phenomena (Shen et al, 2010;Fang et al, 2012;Tefsen et al, 2014;Lendenmann et al, 2015;Cavalheiro et al, 2018;So et al, 2019;Lev et al, 2019).…”
Section: Comparison To Previous Qtl Studies In Cryptococcus and Othermentioning
confidence: 61%
“…This phenomenon is different from previous findings in S. cerevisiae and Cryptococcus neoformans ( Lev et al, 2015 ). In C. neoformans , KCS1 knockout resulted in cell wall integrity defect, and the growth of kcs1 Δ in alternative carbon sources such as glycerol medium was significantly weakened; knockout of the ASP1 / VIP1 did not affect the virulence of the strain and had no effect on cellular function ( Li C. et al, 2016 ; Lev et al, 2019 ). In yeasts, Kcs1 phosphorylates IP 5 into 5-PP-IP 4 and IP 6 into 5-PP-IP 5 (IP 7 ); Vip1 phosphorylates IP 6 into IP 7 isomer 1-PP-IP 5 .…”
Section: Discussionmentioning
confidence: 99%
“…(PP) 2 -IP 4 (IP 8 ) is generated by either Kcs1-mediated phosphorylation of 1-PP-IP 5 or Vip1-mediated phosphorylation of 5-PP-IP 5 ( Banfic et al, 2016 ). But in C. neoformans , Kcs1 mediates the synthesis of PP-IP 5 /IP 7 , and Asp1/Vip1 further synthesize PP 2 -IP 4 /IP 8 ( Lev et al, 2019 ). In C. albicans , how Kcs1 and Vip1 act in the synthesis of inositol polyphosphate have not yet been studied, and this will be the direction of our later research.…”
Section: Discussionmentioning
confidence: 99%